Experimental research of the stress-strain state of reinforced-concrete building in the case of progressive collapse - Руденко, Виктория Владимировна; Шаповалов, Александр Никитович (Eastern-European Journal of Enterprise Technologies, 2015)
An experimental research of the stress-strain state of the seven-story reinforced-concrete layout of the building with the size about 2x2 m and the cell of column 0,5x0,5 m, in case of failure of the middle column of extreme row of the first floor was carried out. For evaluating the operation of the damaged layout of the building, deformations of the neighboring columns, placed in the same cell with a remote column were defined, and movements of floors, located above the dangerous cell were analyzed. Intensive deformation growth in columns adjacent to the removed column and their reduction in neighboring cells was revealed. Deformation growth was in the range of 30-40% compared with deformation growth in a gradual proportional loading, which indicates a promising destruction of the dangerous area without an avalanche process. Such phenomenon of destruction is based on the rational arrangement of stiffening diaphragms. The structural diagram of the building layout was a rigid beamless frame conjugate in the form of rigid unyielding block. The method of loading the layout was carried out using the loading blocks, each weighing on average 60 kg, gradually stacked on the floors. Removal of the column was performed by a special method using a removable conical insert of the middle part of the column.